2021
DOI: 10.12688/f1000research.73210.1
|View full text |Cite
|
Sign up to set email alerts
|

Weak and strong ties and its connection to experts' problem-solving styles in scaffolding students' PBL activities on social media

Abstract: Background: Studies have acknowledged that social media enables students to connect with and learn from experts from different ties available in the students’ personal learning environment (PLE). The inclusion of experts in formal learning activities through social media such as in scaffolding problem-solving activities helps students see the practicality of experts’ thinking in solving real-world problems. However, studies that evaluate experts’ problem-solving styles and how these influence the experts' thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…With regard to the samples, while students were the principal object of study, some works also analysed teachers jointly (Abdullah et al, 2021;Dabbagh & Kitsantas, 2013;Reed, 2013;Wu et al, 2020) or exclusively (Marín-Díaz et al, 2014;Morán-López, 2013) and these tools as an effective continuous training instrument, above all in the case of teaching skills or techniques (Marín-Díaz et al, 2014;Morán-López, 2013). We have also found that in some of the works, other figures also appear such as professional and external experts (Abdullah et al, 2021;Moreira et al, 2017;Pimmer et al, 2018).…”
Section: Educational Contexts and Users Of Social Media In The Config...mentioning
confidence: 67%
See 2 more Smart Citations
“…With regard to the samples, while students were the principal object of study, some works also analysed teachers jointly (Abdullah et al, 2021;Dabbagh & Kitsantas, 2013;Reed, 2013;Wu et al, 2020) or exclusively (Marín-Díaz et al, 2014;Morán-López, 2013) and these tools as an effective continuous training instrument, above all in the case of teaching skills or techniques (Marín-Díaz et al, 2014;Morán-López, 2013). We have also found that in some of the works, other figures also appear such as professional and external experts (Abdullah et al, 2021;Moreira et al, 2017;Pimmer et al, 2018).…”
Section: Educational Contexts and Users Of Social Media In The Config...mentioning
confidence: 67%
“…As has already been seen, some results focused on the valuation of user experiences, users' perceptions (Sweet-Cushman, 2019) or the intention and continuity of use (Arquero et al, 2017). The value of the relationship between instructors and students (Abdullah et al, 2021) and differences in motivation among students (Lau, 2016) are emphasised on occasion and continued analysis of this type is recommended.…”
Section: Discussion Conclusion Implications and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation